ANALISIS PERSEPSI MAHASISWA PENGGUNA LAYANAN PEMBAYARAN KULIAH DENGAN VIRTUAL ACCOUNT MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALYSIS (STUDI KASUS : MAHASISWA UNIVERSITAS GUNADARMA) - Yunianti, Vidya; Prijanto, Budi (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2025)
The outbreak of coronavirus in 2020, making the movement of people restricted so as to encourage digitization in the payment method of tuition in college. The payment of tuition is made using a Virtual Account.This study aims to analyze the perception of students using college payment services using virtual accounts during the Covid-19 pandemic. The population of the study was all active students of Gunadarma University.The sampling measure used the Maximum Likelihood Estimation (MLE) Technique and obtained 160 respondents. The analysis model used is the method of importance performance analysis (IPA) with the dimensions of technology acceptance model (TAM), which is perceived ease of use, perceived usefulness, attitude toward using, behavioral intention and actual usage.The results showed that 20 tam dimensional statement items have an average overall performance rate of 60.88% so it can be categorized well. While in the gap analysis there is still a negative gap of < 0 which indicates that the quality of college payments using virtual accounts still has to be improved again, even so the level of conformity obtained has reached 100%. This shows that in general, tuition payments with virtual accounts have met student expectations. In the paper diagram, in quadrant I there are 3 dimensions whose quality level is still not satisfactory and is a top priority to be evaluated, namely the dimensions of attitude toward using, behavioral intention and actual use.